Silver Diamine Fluoride in Children Using Physiologically Based PK Modeling. (July 2020) - Chen, K.-F.; Milgrom, P.; Lin, Y.S.
Silver diamine fluoride (SDF) is used topically to prevent or arrest dental caries and has been tested clinically in toddlers to elderly adults. Following SDF application, small quantities of silver can be swallowed and absorbed. To monitor silver concentrations, pharmacokinetic studies can be performed. However, pharmacokinetic studies are time-consuming, resource intensive, and challenging to perform in young children. The objective of this study was to develop a physiologically based pharmacokinetic (PBPK) model to predict silver disposition in children. The PBPK model for silver was developed using Simcyp software (version 17.0) based on information obtained from literature sources. The predictive performance of the model was assessed by comparing the predicted PK profiles and parameters with the observed data from published rat and human data following intravenous or oral silver administration. The predicted silver concentrations were within 2-fold of observed blood and tissue silver concentrations in rats and within the 95% confidence interval of observed plasma silver concentrations in healthy human adults. The PBPK model was applied to the pediatric population by accounting for developmental physiological changes. For a given SDF dose, the simulated peak silver concentrations were 5.2-, 4.3-, 2.7-, and 1.3-fold higher in children aged 1 to 2, 2 to 4, 5 to 10, and 12 to 17 y, respectively, compared to adults. As silver is reportedly excreted in the bile, the half-life of silver was comparable in all ages and plasma and tissue silver concentrations were predicted to return to baseline levels within 2 wk after SDF application. The simulation in children suggests that conventional SDF application to teeth to prevent or arrest dental caries results in plasma and tissue silver concentrations lower than toxic concentrations. PBPK modeling offers a novel approach to studying dental exposures in younger children, where pharmacokinetic studies would be difficult to conduct.